Pengaruh Motivasi, Kontrol Perilaku dan Tingkat Pemahaman terhadap Minat Mengikuti Sertifikasi Konsultan Pendamping UMKM Junior - Tri Utari; Dewi Kusuma Wardani; Dini Octoria (Journal on Education, 2024)
Abstract The study aims to determine the direct influence of motivation on economic education students interest to taking the junior MSMEs mentoring consultant occupational certification, the direct influence of perceived behavior control on economic education students interest to taking the junior MSMEs mentoring consultant occupational certification, the direct influence of level of understanding on economic education students interest to taking the junior MSMEs mentoring consultant occupational certification. This research is quantitative study with a population of 195 students and a total sample of 131 Economic Education students from group class off 2018-2020. The sampling technique used was proportional random sampling. Data was collected using questionnaires. Data was analyzed using Multiple Linear Regression calculated wits SPSS application version 26. The results of this study indicate that the variables of the motivation and level of understanding have a positive and significant effect on economic education students interest to taking the junior MSMEs mentoring consultant occupational certification. Meanwhile, perceived behavior control do not affect on economic education students interest to taking the junior MSMEs mentoring consultant occupational certification.